Livelihoods of families engaged in agriculture and livestock farming in the Guatuso canton, Alajuela. Cluster analysis - Valenciano Salazar, Jorge Andrey (2012)
Using cluster analysis, households in the canton of Guatuso, Costa Rica, are classified into three different categories (small, medium, and large producers) based on the types of capital (physical, social, natural, human, and financial) available to them. However, the most common category in the area consists of families with low capital availability, who can be classified as small producers. Furthermore, there is a direct relationship between families’ availability of capital, the scale of production, and market integration; that is, families classified as large producers have greater availability of all forms of capital, which makes them better able to adapt to the conditions of the current international market.